Research of Web Real-Time Communication - the Unified Communication Platform using Node.js Signaling Server - Damayanti, Florensia Unggul (Swiss German University, 2018)
The way of people communicate has been changed from generation. With rapid innovation of technology and the improvement of computer technology, smartphone, tablet and etc., the traditional communication is confronted. However, unified communication born and Web Real-Time Communication as a part of the innovation of communication technology, enhance the way peoples share their thought, feeling and information, in real-time and different place. This research offers an educational foundation and applied research of WebRTC, to leverage unified communication, through WebSocket node.js as the signalling protocol. A system of web real-time communication developed at the end of research to give an understanding and view of the opportunity given by WebRTC technology, such as leverage online distance-learning with a real-time communication, healthcare video conferencing, online video conference, self-service customer care and corporate online meeting.